HUBUNGAN AKTIVITAS FISIK DENGAN SINDROM PREMENSTRUASI PADA SISWI SMP N 3 GAMPING SLEMAN YOGYAKARTA - Dwi Susanti Susanti; Rizki Hasan (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: premenstrual syndrome is a group of symptoms in physical, psychological, emotional and behaviour which occurs to productive woman between 7-10 days before menstruation and finish after the ovulation begins. One of the factor that  cause premenstrual syndrome is  physical activity. Lack of physical activity can cause the Premenstrual  syndrome getting worse. The high percentage of premenstrual syndrome cases on SMPN 3  Gamping students can disturb the learning activity in school.Objective: to know the relation between physical activity and premenstrual syndrome on the students of SMPN 3 Gamping Sleman Yogyakarta.Methods: this research is a quantitative research with cross-sectional and stratified random sampling technique. The subject of this research are 67 samples. The respondence are female students of SMPN 3 Gamping. Data collection using physical activity questionnaire and SPAF. Statistics analysis using Kendall's test tau b.  Results: this research shows that respondence who do moderate physical activities are 48 respodent (71,6 %), and respondence who do not experience menstrual syndrome are  57 respondent (85,1 %). There is no relation between physical activity and premenstrual syndrome p-value is 0,161 > 0,05.Conclusion: there is no relation between physical activity and premenstrual syndrome on SMPN 3 Gamping Yogyakarta Students.